Producing Travel Vlogs as Project-Based Learning to Improve the Speaking Performance of Tourism Industry Students - Rina Rachmawati; Eka Listianing Rahayu; Tri Astuti Handayani (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to find out whether travel vlog production as project-based learning can improve the speaking performance of tourism industry students and identify tourism industry students’ perception of producing travel vlogs as project-based learning. This research employed a mixed-method research design. The quantitative design utilized a pre-experimental design involving a one-group pretest-posttest. Meanwhile, descriptive qualitative was applied to the qualitative design. In collecting data, researchers employed tests and interviews as instruments. The data was evaluated using a t-test to define the hypothesis. Additionally, the analysis of the interview transcript was applied. Producing travel vlogs for project-based learning has improved the speaking performance of tourism industry students. Students can expand their ideas and creativity to produce a travel vlog. Tourism industry students also positively perceived the travel vlog production as project-based learning. Most of the students felt happy with producing travel vlogs as project-based learning. This research provides recommendations to many people to produce more travel vlogs so that tourists can use them as a guide for their travel activities